2011
DOI: 10.1007/s10549-011-1541-z
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism and short-term disability associated with breast cancer

Abstract: Few data exist related to the impact of breast cancer on work absenteeism and short-term disability. This retrospective study estimated the extent and costs of breast cancer-associated production loss using a large medical and pharmacy claims database from a US commercially insured population between January 2003 and December 2007. Women aged ≥ 18 years with ≥ 2 breast cancer diagnoses within 90 days were selected. Controls were matched to cases based on index date (first breast cancer diagnosis), age, region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…In terms of the magnitude of the indirect costs, Fu et al 12 estimated that the indirect costs of overall breast cancer in the US were $4972 in 2009 dollars due to absentiseem and $7199 due to short-term disability per woman within the first year of diagnosis of breast cancer. Our study found lower indirect costs for both sick leave and shortterm disability compared to the Fu et al 12 study: the annual indirect costs per employee were estimated at $1775 due to sick leave/$2383 due to short-term disability among employees with EBC and $3690 due to sick leave/$6166 due to short-term disability for MBC employees, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the magnitude of the indirect costs, Fu et al 12 estimated that the indirect costs of overall breast cancer in the US were $4972 in 2009 dollars due to absentiseem and $7199 due to short-term disability per woman within the first year of diagnosis of breast cancer. Our study found lower indirect costs for both sick leave and shortterm disability compared to the Fu et al 12 study: the annual indirect costs per employee were estimated at $1775 due to sick leave/$2383 due to short-term disability among employees with EBC and $3690 due to sick leave/$6166 due to short-term disability for MBC employees, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been little research related to detailing the indirect costs of MBC/BC. Fu et al 12 assessed the incremental indirect costs associated with breast cancer by quantifying the impact of absenteeism (paid time when absent from work) and short-term disability in the US. The authors found that, for the first year of disease post-diagnosis, breast cancer patients incurred nearly twice the amount of absenteeism-related indirect costs and more than 10-times the short-term disability related indirect costs vs a matched control group.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have previously reported these data. Two US retrospective cohort studies found that working patients with BC had significantly longer periods of absenteeism compared to "control" patients (without BC) [9,22]. However, they observed a shorter period of absenteeism in the year following diagnosis when using an HC approach: about 10 days of sick leave and between 25 and 45 days of short-term disability (according to the severity of the disease).…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning absenteeism and indirect costs are useful for decision-makers when considering cost-of-illness studies or model-based economic evaluations on innovative treatments or screening strategies. Few published studies have focused on the indirect costs of BC and absenteeism, with estimates ranging from $8,068 [9] to $21,086 per patient [10], highlighting the importance of the methodology used and the country in which the study is conducted. In France, only one study has reported the indirect costs associated with adjuvant chemotherapy in BC [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, across all cancer sites, Finkelstein et al 7 estimated that individuals undergoing active cancer care missed an average of 22.3 more workdays per year than those without cancer. Fu et al 8 estimated that privately employed women with breast cancer had an average of 14 days of absenteeism and 46 days of short-term disability attributable to their breast cancer in the first year after diagnosis. There are at least three reasons that our estimates of cancer-attributable days of absenteeism tended to be lower than the estimates from other studies.…”
Section: Discussionmentioning
confidence: 99%